Pengaruh Displin Guru Terhadap Produktifitas Kerja di SMAN 1 Seruyan Tengah Kabupaten Seruyan - Leda Almuqsith; Ari Setiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The objectives to be achieved from this study are to find out how much the Teacher's Discipline on the quality of work at SMAN 1 Seruyan Tengah Seruyan Regency. The method used in this study is a quantitative method with observation techniques, and questionnaires (questionnaires). While the data analysis techniques used in this research are using product moment correlation analysis. Based on the results of research and discussion, teacher discipline has a positive and significant effect on the quality of work of SMU 1 Seruyan Tengah teachers in Seruyan district, where indicators of discipline (x) consist of goals and abilities, role models, reward, justice, Waskat (supervision attached ), Legal Sanctions, Assertiveness, Humanitarian relations have a positive and significant effect on the quality of work consisting of Tangibles (physical evidence), Reliability (reliability), Responsiveness (Assurance), Assurance (assurance and certainty), Empathy (empathy). Based on the results of research and discussion, the authors give advice to employees of Central Seruyan 1 Public High School, which is expected to increase leadership supervision and attention to all teachers in carrying out their duties and expected the existence of reward and punishment from leaders to teachers to remain qualified in carrying out their duties.